Analisis Perlindungan Hukum Bagi Tenaga Pekerja Korban Pelecehan Seksual di Kawasan Industri: Studi Kasus Putusan No 83/Pdt.Sus-PHI/2023/PN Srg - Amira Atsil Abigael Wegni; Novi Wulan Suci; Tabina Belinda; Citra Hayu Khatintri (Jurnal Hukum dan Sosial Politik, 2024)
This research analyzes legal protection for workers who are victims of sexual harassment in industrial areas, with a case study of decision number 83/Pdt.Sus-PHI/2023/PN Srg. Legal protection is an effort to create a sense of security for victims from harassment and threats, which are divided into preventive and repressive forms. Based on Law Number 13 of 2003 concerning Employment, this protection covers basic workers' rights, including protection from sexual harassment. This case study illustrates the implementation and challenges in implementing the law at PT Nikomas Gemilang, which involved physical sexual harassment by one male worker against several female workers. The court's decision to reject the perpetrator's lawsuit shows the importance of effective legal protection. The research results show that existing legal protection is not optimal and requires strengthening internal company policies as well as supervision from the government to create a safe and conducive work environment.